Composite negative electrode material and preparation method and application thereof
By covering the composite of porous titanium oxide, carbon nanotubes and lithium phenylsulfonate compounds on the graphite surface of the lithium-ion battery, the limitations of existing materials in terms of first-time efficiency and fast charging performance improvements are solved, and high cycle performance, rate performance and safety performance are improved.
Patent Information
- Application Number
- CN202411818888.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The fast-charging anode materials of existing lithium-ion batteries have limitations in improving first-time efficiency and fast-charging performance. The main reason is that the coating material has a small layer spacing and low ionic conductivity, which leads to large expansion during the charging and discharging process, affecting the material's rate performance.
By covering the composite of porous titanium oxide, carbon nanotubes and lithium phenylsulfonate compounds on the graphite surface, the large layer spacing of titanium oxide and the strong solvation ability of lithium phenylsulfonate can improve the electron and ion transmission rate of the material, and improve the rate performance and first-time efficiency.
The high electron and ion transmission rate of composite negative electrode materials is achieved, which improves the material's circulation performance, rate performance and fast charging performance, while improving safety performance.
Smart Images

Figure CN119650644A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a composite negative electrode material and a preparation method and application thereof. Background Art
[0002] At present, the fast-charging negative electrode material used in lithium-ion batteries is mainly artificial graphite, which is mainly composed of graphite and amorphous carbon coated on its surface. However, due to the low specific capacity of the coated amorphous carbon itself, low first-time efficiency and small material interlayer spacing, the first-time efficiency of the material is low and the improvement of the fast-charging performance of the material is limited. Some researchers have improved the fast-charging performance of the material by coating the surface of the material with fast ion conductors. Although the ion conductivity of the obtained material is improved, the improvement of the first-time efficiency of the material is not large. In addition, due to the low interlayer spacing of the coating layer material and its low ion conductivity, it expands too much during the charge and discharge process, resulting in limited improvement in the fast-charging performance of the material.
[0003] Therefore, how to optimize the coating material and its structure to enhance the electron and ion transmission rate of the material and improve the rate performance of the material is crucial to the development of batteries.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] An object of the present invention is to provide a composite negative electrode material with high electron and ion transmission rate, good cycle performance and rate performance, and high safety performance.
[0006] Another object of the present invention is to provide a method for preparing a composite negative electrode material, which is simple, easy to operate and environmentally friendly.
[0007] Another object of the present invention is to provide a negative electrode sheet.
[0008] Another object of the present invention is to provide a battery.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A composite negative electrode material comprises a core matrix and a composite layer arranged on at least part of the surface of the core matrix; the core matrix comprises graphite; the composite layer comprises a composite of porous titanium oxide, conductive carbon material and lithium phenylsulfonate compound.
[0011] In some embodiments, in the composite negative electrode material, the mass fraction of the composite layer is 2% to 8%.
[0012] In some embodiments, the conductive carbon material includes one or more of carbon nanotubes, graphene, and conductive carbon black.
[0013] In some embodiments, the lithium phenylsulfonate includes one or more of lithium 3-aminobenzenesulfonate, lithium m-aminobenzenesulfonate, lithium isopropylbenzenesulfonate, lithium cumenesulfonate, and lithium p-toluenesulfonate.
[0014] In some embodiments, the specific surface area of the composite negative electrode material is 3 to 4.5 m 2 / g.
[0015] In some embodiments, the interlayer spacing of the composite negative electrode material is 0.3730-0.3810 nm.
[0016] In some embodiments, the ionic conductivity of the composite negative electrode material is 1×10 -9 ~9×10 -9 S / cm.
[0017] The method for preparing the composite negative electrode material as described above comprises the following steps:
[0018] A first mixed system of a titanium source, a dispersant, a conductive agent solution, graphite, an alkali solution and a first solvent is subjected to a hydrothermal reaction treatment, and the solid matter after the reaction is collected and sintered to obtain a first material; the first material, lithium phenylsulfonate and an organic solvent are mixed and dried to obtain a composite negative electrode material.
[0019] In some embodiments, the titanium source includes titanium chloride.
[0020] In some embodiments, the dispersant includes at least one of sodium lauryl sulfate, polyvinyl alcohol, and polyacetyl pyrrolidone.
[0021] In some embodiments, the conductive agent solution includes at least one of a carbon nanotube conductive liquid, a graphene conductive liquid, and a carbon black conductive liquid; and the concentration of the conductive agent solution is 1% to 5%.
[0022] In some embodiments, the alkali solution includes at least one of n,n-dimethylethanolamine, diethylaminoethanol, dimethylaminopropylamine, dimethylamine and diethylamine.
[0023] In some embodiments, the mass ratio of the titanium source, the dispersant, the conductive agent solution, the graphite, and the alkaline solution is (50-100):(10-50):(10-50):1000:(100-300).
[0024] In some embodiments, the mass ratio of the titanium source to the first solvent is (50-100):(600-1500).
[0025] In some embodiments, the preparation method of the mixed system specifically includes: dispersing the titanium source and the dispersant in the first solvent, wherein the total mass content of the titanium source and the dispersant is 8% to 12%, and then adding the conductive agent solution, the graphite and the alkali solution.
[0026] In some embodiments, the temperature of the hydrothermal reaction treatment is 100 to 200° C., and the time of the hydrothermal reaction treatment is 1 to 6 hours.
[0027] In some embodiments, the sintering temperature is 500-800° C., and the sintering time is 1-6 hours.
[0028] In some embodiments, a drying treatment is further included between the hydrothermal reaction treatment and the sintering treatment; the temperature of the drying treatment is 60 to 90° C., and the time of the drying treatment is 15 to 25 hours.
[0029] In some embodiments, the lithium phenyl sulfonate includes at least one of lithium 3-aminobenzenesulfonate, lithium m-aminobenzenesulfonate, lithium isopropylbenzenesulfonate, lithium cumenesulfonate, and lithium p-toluenesulfonate.
[0030] In some embodiments, the organic solvent includes at least one of ethanol, ether, carbon tetrachloride and tetrahydrofuran.
[0031] In some embodiments, the mass ratio of the lithium phenylsulfonate to the first material is (5-10):1000.
[0032] In some embodiments, the mass ratio of the lithium phenylsulfonate to the organic solvent is (5-10):100.
[0033] In some embodiments, the drying comprises spray drying, the inlet temperature of the spray drying is 200-240° C., the outlet temperature of the spray drying is 100-130° C., the flow rate of the spray drying is 0.1-0.5 kg / h, and the time of the spray drying is 1-5 h.
[0034] A negative electrode sheet comprises the composite negative electrode material or the composite negative electrode material prepared by the method for preparing the composite negative electrode material.
[0035] A battery comprises the negative electrode sheet.
[0036] An electrical device comprises the battery.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The composite negative electrode material of the present invention is a composite of porous titanium oxide, carbon nanotubes and lithium phenylsulfonate compounds coated on the surface of graphite. The fast charging performance and cycle performance of the material are improved by utilizing the large interlayer spacing, high voltage platform and low expansion of titanium oxide itself. The strong solvation ability of lithium phenylsulfonate itself can be used to increase the diffusion rate of lithium ions during charging and discharging, thereby improving the rate performance. At the same time, lithium phenylsulfonate is coated on the surface to reduce defects, reduce irreversible capacity loss and improve the initial efficiency. Through the coating of the composite layer, the cycle performance and rate performance of the composite negative electrode material can be improved, and the fast charging performance and safety performance are good.
[0039] (2) The preparation method of the composite negative electrode material of the present invention is simple and easy. The titanium source, dispersant, conductive agent solution, graphite and alkali solution are mixed and then subjected to hydrothermal reaction treatment. The titanium source and OH in the solution are - Reaction to generate Ti(OH)3, which is then sintered to generate porous titanium oxide. The porous titanium oxide and the conductive agent are reacted together by a hydrothermal reaction, and the conductive agent can be uniformly doped in the porous titanium oxide. The first material, lithium phenylsulfonate and an organic solvent are further mixed and dried, and lithium phenylsulfonate, porous titanium oxide and conductive carbon materials form a composite. Lithium phenylsulfonate contains sulfonate groups and has a strong solvation ability, which is conducive to improving the lithium ion insertion and extraction rate and improving the rate. Through the coordination of various steps, the obtained composite negative electrode material has a suitable specific surface area, interlayer spacing, good conductivity, good cycle stability, and good fast charging performance.
[0040] (3) The battery of the present invention has excellent cycle performance, rate performance, good fast charging performance and high safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is a scanning electron microscope (SEM) image of the composite negative electrode material in Example 1. DETAILED DESCRIPTION
[0043] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0044] According to one aspect of the present invention, the present invention relates to a composite negative electrode material, comprising a core matrix and a composite layer arranged on at least a portion of the surface of the core matrix; the core matrix comprises graphite; the composite layer comprises a composite of porous titanium oxide, conductive carbon material and lithium phenylsulfonate compound.
[0045] The composite negative electrode material of the present invention is a composite of porous titanium oxide, carbon nanotubes and lithium phenylsulfonate compounds coated on the surface of graphite, and the fast charging performance and the cycle performance of the material are improved by utilizing the large interlayer spacing, high voltage platform and low expansion of titanium oxide itself; the strong solvation ability of lithium phenylsulfonate itself is utilized to increase the diffusion rate of lithium ions during the charge and discharge process and improve the rate performance; at the same time, the lithium phenylsulfonate is coated on the surface to reduce defects, reduce irreversible capacity loss, and improve the initial efficiency; through the coating of the composite layer, the cycle performance and rate performance of the composite negative electrode material can be improved, the fast charging performance is good, and the safety performance is high.
[0046] In some embodiments, in the composite negative electrode material, the mass fraction of the composite layer is 2% to 8%, including but not limited to 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 7%, 8%, etc., or any range between the two. In the composite negative electrode material of the present invention, the composite layer with an appropriate mass content is more conducive to improving the overall electrochemical performance of the material.
[0047] In some embodiments, the conductive carbon material includes one or more of carbon nanotubes, graphene and conductive carbon black, such as a combination of carbon nanotubes and graphene, a combination of graphene and conductive carbon black, and the like.
[0048] In some embodiments, the lithium phenylsulfonate includes one or more of lithium 3-aminobenzenesulfonate, lithium m-aminobenzenesulfonate, lithium isopropylbenzenesulfonate, lithium cumenesulfonate and lithium p-toluenesulfonate, for example, a combination of lithium 3-aminobenzenesulfonate and lithium m-aminobenzenesulfonate, a combination of lithium isopropylbenzenesulfonate and lithium cumenesulfonate, a combination of lithium isopropylbenzenesulfonate, lithium cumenesulfonate and lithium p-toluenesulfonate, etc.
[0049] In some embodiments, the composite negative electrode material of the present invention has a suitable specific surface area of 3 to 4.5 m 2 / g, including but not limited to 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.2m 2 / g, 4.5m 2 / g, etc., or any range between the two.
[0050] In some embodiments, the composite negative electrode material of the present invention has a suitable interlayer spacing of 0.3730 to 0.3810 nm, including but not limited to 0.3730 nm, 0.3740 nm, 0.3750 nm, 0.3760 nm, 0.3800 nm, 0.3810 nm, etc., or any range between two values.
[0051] In some embodiments, the ionic conductivity of the composite negative electrode material of the present invention is 1×10 -9 ~9×10 -9 S / cm, for example 1×10 -9 S / cm, 3×10 -9 S / cm, 5×10 -9 S / cm, 8×10 -9 S / cm, etc., or any range between the two. The composite negative electrode material of the present invention has excellent ion conductivity.
[0052] According to another aspect of the present invention, the present invention also relates to a method for preparing the composite negative electrode material as described above, comprising the following steps:
[0053] The first mixed system formed by the titanium source, the dispersant, the conductive agent solution, the graphite and the alkali solution is subjected to a hydrothermal reaction treatment, and the solids after the reaction are collected and sintered to obtain the first material. The first material, lithium phenylsulfonate and the organic solvent are mixed and dried to obtain a composite negative electrode material.
[0054] The preparation method of the composite negative electrode material of the present invention is simple and easy. The titanium source, dispersant, conductive agent solution, graphite and alkali solution are mixed and then subjected to hydrothermal reaction treatment. The titanium source and OH in the solution are - Reaction to generate Ti(OH)3, which is then sintered to generate porous titanium oxide. The porous titanium oxide and the conductive agent are reacted together by a hydrothermal reaction, and the conductive agent can be uniformly doped in the porous titanium oxide. The first material, lithium phenylsulfonate and an organic solvent are further mixed and dried, and lithium phenylsulfonate, porous titanium oxide and conductive carbon materials form a composite. Lithium phenylsulfonate contains sulfonate groups and has a strong solvation ability, which is conducive to improving the lithium ion insertion and extraction rate and improving the rate. Through the coordination of various steps, the obtained composite negative electrode material has a suitable specific surface area, interlayer spacing, good conductivity, good cycle stability, and good fast charging performance.
[0055] In some embodiments, the titanium source includes titanium chloride.
[0056] In some embodiments, the dispersant includes one or more of sodium lauryl sulfate, polyvinyl alcohol and polyacetyl pyrrolidone, such as sodium lauryl sulfate and polyvinyl alcohol, polyvinyl alcohol and polyacetyl pyrrolidone, and the like.
[0057] In some embodiments, the conductive agent solution includes at least one of a carbon nanotube conductive liquid, a graphene conductive liquid, and a carbon black conductive liquid; the concentration of the conductive agent solution is 1% to 5%, for example, 1%, 2%, 3%, 5%, etc.
[0058] In some embodiments, the alkali solution includes one or more of n,n-dimethylethanolamine, diethylaminoethanol, dimethylaminopropylamine, dimethylamine and diethylamine, for example, a combination of n,n-dimethylethanolamine and diethylaminoethanol, a combination of dimethylamine and diethylamine, a combination of diethylaminoethanol, dimethylaminopropylamine and dimethylamine, and the like.
[0059] In some embodiments, the mass ratio of titanium source, dispersant, conductive agent solution, graphite and alkali solution is (50-100): (10-50): (10-50): 1000: (100-300), including but not limited to 50: 10: 10: 1000: 100, 60: 15: 15: 1000: 200, 60: 25: 25: 1000: 200, 70: 30: 30: 1000: 250, 100: 50: 50: 1000: 300, etc. The present invention adopts suitable titanium source, dispersant, conductive agent solution, graphite and alkali solution in suitable mass ratio, which is more conducive to the performance of the mixed system and improves the electrochemical performance of the final composite negative electrode material.
[0060] In some embodiments, the mass ratio of the titanium source to the first solvent is (50-100): (600-1500), such as 50:600, 60:700, 70:1000, 80:1200, 100:1500, etc. The first solvent of the present invention adopts an appropriate dosage ratio, which is more conducive to sufficient mixing of the materials and is conducive to the subsequent hydrothermal reaction. The first solvent includes water, such as deionized water.
[0061] In some embodiments, the preparation method of the mixed system specifically includes: dispersing the titanium source and the dispersant in water, the total mass content of the titanium source and the dispersant is 8% to 12% (8%, 8.5%, 9%, 9.5%, 10%, 12%, etc.), and then adding a conductive agent solution, graphite and alkali solution.
[0062] In some embodiments, the hydrothermal reaction treatment is carried out in an autoclave, and the temperature of the hydrothermal reaction treatment is 100-200°C, including but not limited to 100°C, 110°C, 120°C, 130°C, 150°C, 170°C, 180°C, 200°C, etc., or any range between the two. The time of the hydrothermal reaction treatment is 1-6h, such as 1h, 2h, 3h, 4h, 5h or 6h, etc., or any range between the two. Through a suitable hydrothermal reaction temperature, TI(OH)3 is obtained and coated on the surface of graphite.
[0063] In some embodiments, the sintering temperature is 500-800°C, including but not limited to 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, or any range between the two. The sintering time is 1-6h, including but not limited to 1h, 2h, 3h, 4h, 5h, 6h, or any range between the two. The present invention generates porous titanium oxide by suitable sintering conditions, and the conductive agent is uniformly doped in the porous titanium oxide to form a porous titanium oxide / conductive agent coating layer on the surface of graphite.
[0064] In some embodiments, a drying treatment is further included between the hydrothermal reaction treatment and the sintering treatment; the drying treatment temperature is 60 to 90°C, including but not limited to 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc., or any range between the two. The drying treatment time is 15 to 25 hours, including but not limited to 15 hours, 18 hours, 20 hours, 24 hours, 25 hours, etc. Appropriate drying treatment can further remove moisture.
[0065] In some embodiments, the lithium phenyl sulfonate includes at least one of lithium 3-aminobenzenesulfonate, lithium m-aminobenzenesulfonate, lithium isopropylbenzenesulfonate, lithium cumenesulfonate and lithium p-toluenesulfonate, for example, a combination of lithium 3-aminobenzenesulfonate and lithium m-aminobenzenesulfonate, a combination of lithium isopropylbenzenesulfonate and lithium cumenesulfonate, a combination of lithium isopropylbenzenesulfonate, lithium cumenesulfonate and lithium p-toluenesulfonate, and the like.
[0066] In some embodiments, the organic solvent includes one or more of ethanol, diethyl ether, carbon tetrachloride and tetrahydrofuran, such as a combination of ethanol and diethyl ether, a combination of diethyl ether, carbon tetrachloride and tetrahydrofuran, and the like.
[0067] In some embodiments, the mass ratio of lithium phenylsulfonate to the first material is (5-10):1000, such as 5:1000, 5.5:1000, 6:1000, 7:1000, 8:1000, 9:1000 or 10:1000, etc. The lithium phenylsulfonate and the first material of the present invention adopt a suitable mass ratio, which is more conducive to ensuring the appropriate content of lithium phenylsulfonate in the composite particles and better compounding with the conductive agent and porous titanium oxide.
[0068] In some embodiments, the mass ratio of lithium phenylsulfonate to the organic solvent is (5-10):100, 5:1000, 5.5:1000, 6:1000, 7:1000, 9:1000 or 10:1000, etc. The present invention uses a suitable organic solvent to ensure that the materials are fully dispersed and mixed, so as to facilitate the electrochemical performance of the final composite negative electrode material.
[0069] In some embodiments, drying includes spray drying, the inlet temperature of spray drying is 200-240°C, such as 200°C, 210°C, 220°C or 240°C, etc., the outlet temperature of spray drying is 100-130°C, such as 100°C, 120°C or 130°C, etc., the flow rate of spray drying is 0.1-0.5kg / h, such as 0.1kg / h, 0.2kg / h, 0.3kg / h, 0.5kg / h, etc., and the time of spray drying is 1-5h, such as 1h, 2h, 3h, 4h or 5h, etc. The present invention adopts suitable spray drying conditions to obtain a composite negative electrode material with better performance.
[0070] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the above-mentioned composite negative electrode material, or a composite negative electrode material prepared by the above-mentioned method for preparing the composite negative electrode material.
[0071] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode layer located on at least one side surface of the negative electrode current collector, and the negative electrode layer comprises the above-mentioned composite negative electrode material, a conductive agent and a binder.
[0072] According to another aspect of the present invention, the present invention also relates to a battery, comprising the above-mentioned negative electrode sheet.
[0073] The battery of the present invention has excellent cycle performance, rate performance, good fast charging performance and high safety.
[0074] In some embodiments, a battery includes the above-mentioned negative electrode sheet, positive electrode sheet, separator and electrolyte.
[0075] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the above-mentioned battery. The electric device includes a laptop computer, an electric car, an electric tool, and the like.
[0076] The following is further explained in conjunction with specific embodiments and comparative examples.
[0077] Example 1
[0078] A method for preparing a composite negative electrode material comprises the following steps:
[0079] (1) 80 g of titanium chloride and 30 g of sodium dodecyl sulfate were dispersed in 1100 g of deionized water to prepare a 10 wt% solution, and then 30 g of a 3 wt% carbon nanotube conductive agent solution was added, and then 1000 g of artificial graphite was added and dispersed evenly, and then 200 gn of n-dimethylethanolamine was added dropwise to mix evenly, and then transferred to a high-pressure reactor, and a hydrothermal reaction was carried out at a temperature of 150° C. for 3 h, filtered, and vacuum dried at 80° C. for 24 h, and then the obtained material was sintered at a temperature of 650° C. for 3 h to obtain a first material.
[0080] (2) 8 g of lithium 3-aminobenzenesulfonate was added to 100 g of dimethyl carbonate organic solvent and dispersed evenly, then 100 g of the first material was added and dispersed evenly, and spray-dried (inlet temperature was 220° C., outlet temperature was 120° C., flow rate was 0.3 kg / h, and time was 3 h) to obtain a composite negative electrode material.
[0081] Example 2
[0082] A method for preparing a composite negative electrode material comprises the following steps:
[0083] (1) 50 g of titanium chloride and 10 g of polyvinyl alcohol are dispersed in 600 g of deionized water to prepare a 10 wt% solution, and then 10 g of a 5 wt% graphene conductive agent solution is added, and then 1000 g of artificial graphite is added and dispersed evenly, and then 100 g of diethylaminoethanol is added dropwise to mix evenly, and the mixture is transferred to a high-pressure reactor, and a hydrothermal reaction is carried out at a temperature of 100 ° C. for 6 h, filtered, and vacuum dried at 80 ° C. for 24 h, and then the obtained material is sintered at a temperature of 500 ° C. for 6 h to obtain a first material.
[0084] (2) 5 g of lithium isopropylbenzene sulfonate was added to 100 g of dimethyl carbonate organic solvent and dispersed evenly, then 100 g of the first material was added and dispersed evenly, and spray-dried (inlet temperature was 220° C., outlet temperature was 120° C., flow rate was 0.1 kg / h, and time was 5 h) to obtain a composite negative electrode material.
[0085] Example 3
[0086] A method for preparing a composite negative electrode material comprises the following steps:
[0087] (1) 100 g of titanium chloride and 50 g of polyacetyl pyrrolidone are dispersed in 1500 g of deionized water to prepare a 10 wt% solution, and then 50 g of a 5 wt% superconducting carbon black conductive agent solution is added, and then 1000 g of artificial graphite is added and dispersed evenly, and then 300 g of dimethylaminopropylamine is added dropwise and mixed evenly, and then transferred to a high-pressure reactor, and a hydrothermal reaction is carried out at a temperature of 200° C. for 1 hour, filtered, and vacuum dried at 80° C. for 24 hours, and then the obtained material is sintered at a temperature of 800° C. for 1 hour to obtain a first material.
[0088] (2) 10 g of lithium m-aminobenzenesulfonate was added to 100 g of dimethyl carbonate organic solvent and dispersed evenly, then 100 g of the first material was added and dispersed evenly, and spray-dried (inlet temperature was 220° C., outlet temperature was 120° C., flow rate was 0.5 kg / h, and time was 1 h) to obtain a composite negative electrode material.
[0089] Example 4
[0090] A method for preparing a composite negative electrode material comprises the following steps:
[0091] (1) 75 g of titanium chloride and 45 g of polyacetyl pyrrolidone are dispersed in 1200 g of deionized water to prepare a 10 wt% solution, and then 15 g of a 5 wt% superconducting carbon black conductive agent solution and 20 g of a 5 wt% carbon nanotube are added, and then 1000 g of artificial graphite is added and dispersed evenly, and then 260 g of dimethylaminopropylamine is added dropwise and mixed evenly, and the mixture is transferred to a high-pressure reactor, and a hydrothermal reaction is carried out at a temperature of 160° C. for 2 h, filtered, and vacuum dried at 70° C. for 24 h, and then the obtained material is sintered at a temperature of 670° C. for 2.5 h to obtain a first material.
[0092] (2) 3.5 g of lithium m-aminobenzenesulfonate and 4 g of lithium p-toluenesulfonate were added to 100 g of dimethyl carbonate organic solvent and dispersed evenly, and then 100 g of the first material was added and dispersed evenly, and spray-dried (inlet temperature was 220° C., outlet temperature was 120° C., flow rate was 0.3 kg / h, and time was 3 h) to obtain a composite negative electrode material.
[0093] Example 5
[0094] A method for preparing a composite negative electrode material, which differs from Example 4 in that:
[0095] In step (2), 1.5 g of lithium m-aminobenzenesulfonate, 1.5 g of lithium p-toluenesulfonate and 3.5 g of lithium 3-aminobenzenesulfonate are added to 100 g of dimethyl carbonate organic solvent and dispersed evenly, then 100 g of the first material is added and dispersed evenly, and spray dried (inlet temperature is 220° C., outlet temperature is 120° C., flow rate is 0.3 kg / h, time is 3 h) to obtain a composite negative electrode material.
[0096] Comparative Example 1
[0097] A method for preparing a composite negative electrode material, which is different from Example 1 in that:
[0098] In step (1), titanium chloride and n-dimethylethanolamine are not added, that is, titanium oxide is not prepared.
[0099] Comparative Example 2
[0100] A method for preparing a composite negative electrode material, which is different from Example 1 in that:
[0101] The steps (1) of Example 1 are followed to obtain a first material as a negative electrode material.
[0102] Experimental example
[0103] 1. SEM test
[0104] The composite negative electrode material prepared in Example 1 was subjected to SEM testing, and the results are as follows Figure 1As shown. Figure 1 It can be seen that the composite negative electrode material has a granular structure with slight adhesion, a particle size between 10 and 15 μm, and a uniform size distribution.
[0105] 2. Performance test of composite negative electrode materials
[0106] The specific surface area of the above negative electrode materials was tested according to the standard GB / T-24533-2019 "Graphite negative electrode materials for lithium-ion batteries". The ionic conductivity test method was tested using the AC impedance method. XRD tested the interlayer spacing of the powder material. The test results are shown in Table 1.
[0107] Table 1 Test results of composite negative electrode materials
[0108]
[0109]
[0110] 3. Button battery test
[0111] The composite negative electrode materials prepared in the examples and comparative examples were assembled into button-type batteries according to the following methods:
[0112] Add binder, conductive agent and solvent to the composite negative electrode material, stir and mix evenly to form negative electrode slurry, binder is polyvinylidene fluoride, conductive agent is SP conductive agent, solvent is NMP, weight ratio of negative electrode material, SP conductive agent, polyvinylidene fluoride and NMP is 95:1:4:220, negative electrode slurry is coated on copper foil, dried, rolled and cut to obtain negative electrode sheet. Metal lithium sheet is used as counter electrode; polyethylene (PE) film is used as separator; electrolyte is LiPF6 solution, LiPF6 concentration is 1.3 mol / L, solvent is EC and DEC, volume ratio of EC and DEC is 1:1; battery assembly is carried out in an argon-filled glove box.
[0113] The button cells were installed on the Wuhan Blue Electric CT2001A battery tester, and charged and discharged at a rate of 0.1C. The charge and discharge voltage range was 0.005V-2.0V, and the first discharge capacity and first discharge efficiency were measured. The 1C rate discharge capacity was tested, and the rate performance (1C / 0.1C), cycle performance (0.1C / 0.1C, 100 weeks) and low temperature charging DCR (-20℃, 50% SOC) were calculated.
[0114] The performance test results of the button battery are shown in Table 2.
[0115] Table 2 Performance test results of button batteries
[0116]
[0117]
[0118] 4. Soft pack battery test
[0119] The negative electrode was prepared using the composite negative electrode materials prepared in each embodiment and comparative example, the positive electrode was prepared using NCM111 as the positive electrode material, a 2Ah soft-pack battery was prepared using LiPF6 solution as the electrolyte (the solvent was EC and DEC, the volume ratio was 1:1, the concentration was 1.3 mol / L), and celegard2400 as the separator.
[0120] When preparing the negative electrode, a binder, a conductive agent and a solvent are added to the negative electrode material, the binder is LA132 binder, the conductive agent is SP conductive agent, the solvent is double distilled water, and the weight ratio of the negative electrode material, SP conductive agent, LA132 binder and double distilled water is 95:1:4:220. The mixture is stirred and mixed evenly to form a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, dried, rolled, and cut to obtain a negative electrode sheet.
[0121] When preparing the positive electrode, a binder, a conductive agent, and a solvent are added to the positive electrode material, wherein the binder is PVDF, the conductive agent is SP, and the solvent is N-methylpyrrolidone. The weight ratio of the positive electrode material, the conductive agent, the binder, and the solvent is 93:3:4:140; the mixture is stirred and mixed evenly to form a positive electrode slurry, and the positive electrode slurry is coated on an aluminum foil, dried, rolled, and cut to form a positive electrode sheet.
[0122] 1. Rate performance test
[0123] The charge and discharge voltage range is 2.8~4.35V, the test temperature is 25±3.0℃, and the charging is performed at 1.0C, 2.0C, 3.0C, and 5.0C, and the discharge is performed at 1.0C. The constant current ratio and temperature of the battery under different charging modes are tested. The results are shown in Table 3:
[0124] Table 3 Rate performance
[0125]
[0126] 2. Cycle performance test
[0127] The soft-pack batteries made of the composite negative electrode materials in the embodiments and comparative examples were subjected to the following experiment: at a charge and discharge rate of 2C / 2C and a voltage range of 2.8-4.35V, 100, 300, and 500 charge and discharge cycles were performed in sequence to test their capacity retention rate. The results are shown in Table 4.
[0128] Table 4 Cyclic performance test
[0129]
[0130] From the above, it can be seen that the composite negative electrode materials prepared in each embodiment of the present invention have suitable specific surface area, interlayer spacing, high ion conductivity, and the first efficiency and rate performance of the button-type battery obtained are good, which are better than those of comparative examples 1-2. The reasons include: the surface of the graphite material of each embodiment is coated with porous titanium oxide, which takes advantage of its own large interlayer spacing, and is combined with conductive carbon and lithium phenylsulfonate to increase the interlayer spacing and diffusion coefficient of the material, reduce the defects of the material, and improve the first efficiency and its lithium ion diffusion rate.
[0131] The composite negative electrode materials of each embodiment of the present invention have good rate performance and cycle performance of the soft-pack battery; the good rate performance means that the composite negative electrode material has good fast charging performance. The reasons include: the porous titanium oxide coated on the surface of the material has a large interlayer spacing, and with other materials in the composite layer, it can increase the insertion and extraction rate of lithium ions during the charging and discharging process and improve the constant current ratio of the material; the cycle performance of the soft-pack battery obtained by the composite negative electrode materials of each embodiment of the present invention is significantly better than that of the comparative example at all stages.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite negative electrode material, characterized in that: It comprises a core matrix and a composite layer arranged on at least a part of the surface of the core matrix; The core matrix includes graphite; The composite layer includes a composite of porous titanium oxide, a conductive carbon material and a lithium phenylsulfonate compound.
2. The composite negative electrode material according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) In the composite negative electrode material, the mass fraction of the composite layer is 2% to 8%; (2) The conductive carbon material includes one or more of carbon nanotubes, graphene and conductive carbon black; (3) Lithium phenylsulfonate includes one or more of lithium 3-aminobenzenesulfonate, lithium m-aminobenzenesulfonate, lithium isopropylbenzenesulfonate, lithium cumenesulfonate and lithium p-toluenesulfonate.
3. The composite negative electrode material according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) The specific surface area of the composite negative electrode material is 3 to 4.5 m 2 / g; (2) The interlayer spacing of the composite negative electrode material is 0.3730 to 0.3810 nm; (3) The ionic conductivity of the composite negative electrode material is 1×10 -9 ~9×10 -9 S / cm.
4. The method for preparing a composite negative electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: subjecting a first mixed system of a titanium source, a dispersant, a conductive agent solution, graphite, an alkali solution and a first solvent to a hydrothermal reaction, collecting a solid product after the reaction and subjecting it to a sintering treatment to obtain a first material; The first material, lithium phenylsulfonate and an organic solvent are mixed and dried to obtain a composite negative electrode material.
5. The method for preparing a composite negative electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (6): (1) The titanium source includes titanium chloride; (2) the dispersant comprises at least one of sodium lauryl sulfate, polyvinyl alcohol and polyacetyl pyrrolidone; (3) The conductive agent solution includes at least one of a carbon nanotube conductive solution, a graphene conductive solution and a carbon black conductive solution; the concentration of the conductive agent solution is 1% to 5%; (4) the alkali solution comprises at least one of n,n-dimethylethanolamine, diethylaminoethanol, dimethylaminopropylamine, dimethylamine and diethylamine; (5) The mass ratio of the titanium source, the dispersant, the conductive agent solution, the graphite and the alkali solution is (50-100):(10-50):(10-50):1000:(100-300); (6) The mass ratio of the titanium source to the first solvent is (50-100):(600-1500).
6. The method for preparing a composite negative electrode material according to claim 4 or 5, characterized in that: Contains at least one of the following features (1) to (4): (1) The preparation method of the mixed system specifically comprises: dispersing the titanium source and the dispersant in the first solvent, wherein the total mass content of the titanium source and the dispersant is 8% to 12%, and then adding the conductive agent solution, the graphite and the alkali solution; (2) The temperature of the hydrothermal reaction treatment is 100 to 200° C., and the time of the hydrothermal reaction treatment is 1 to 6 hours; (3) The sintering temperature is 500 to 800° C. and the sintering time is 1 to 6 hours; (4) A drying treatment is further included between the hydrothermal reaction treatment and the sintering treatment; the temperature of the drying treatment is 60 to 90° C., and the time of the drying treatment is 15 to 25 hours.
7. The method for preparing a composite negative electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (5): (1) The lithium phenylsulfonate comprises at least one of lithium 3-aminobenzenesulfonate, lithium m-aminobenzenesulfonate, lithium isopropylbenzenesulfonate, lithium cumenesulfonate and lithium p-toluenesulfonate; (2) the organic solvent comprises at least one of ethanol, ether, carbon tetrachloride and tetrahydrofuran; (3) The mass ratio of the lithium phenylsulfonate to the first material is (5-10):1000; (4) The mass ratio of the lithium phenylsulfonate to the organic solvent is (5-10):100; (5) The drying includes spray drying, the inlet temperature of the spray drying is 200-240°C, the outlet temperature of the spray drying is 100-130°C, the flow rate of the spray drying is 0.1-0.5 kg / h, and the time of the spray drying is 1-5 hours.
8. A negative electrode sheet, characterized in that: The invention comprises the composite negative electrode material according to any one of claims 1 to 3, or a composite negative electrode material prepared by the method for preparing the composite negative electrode material according to any one of claims 4 to 7.
9. A battery, characterized in that: Includes the negative electrode sheet as described in claim 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.
Citation Information
Patent Citations
Nano titanium dioxide coated graphite lithium ion battery negative electrode material and preparation method thereof
CN108574098A
Negative electrode material and preparation method thereof, negative electrode plate and battery
CN114551836A
Titanium dioxide / graphite oxide composite material as well as preparation method and application thereof
CN115094478A
Negative electrode material, preparation method thereof and lithium ion battery
CN116314776A
Spherical carbon-based negative electrode composite material and preparation and application thereof
CN118630187A